Coupling Scientific and Humanistic Approaches to Address Wicked Environmental Problems of the Twenty-first Century: Collaborating in an Acoustic Community Nexus - Post, Jennifer C.; Pijanowski, Bryan C. (MUSICultures, 2019)
Addressing serious environmental challenges, or wicked problems, locally and globally, we argue here that working collaboratively as scientist and humanist we are in a strategic position to help address biodiversity crises. We outline synergies that combine the strengths, tools, and fresh perspectives of soundscape ecology and sound studies in ethnomusicology. Our unique collaboration places sound at the core of our process but utilizes a community acoustics lens to bring both the sounds of nature and those of people together to couple our epistemologies, methodologies, and deep commitment to addressing the ecological needs today.